FRI0336 Effectiveness of Abatacept, Rituximab or A TNFI after Failure of the First Tnfi: Results of A Multi-Centered Pragmatic Rct. (10th June 2014) - Manders, S.; Kievit, W.; Adang, E.; Brus, H.; Bernelot Moens, H.; Hartkamp, A.; Hendriks, L.; Vonkeman, H.; Brouwer, E.; Westhovens, R.; Visser, H.; van de Laar, M.; et al.
Abstract : Background: The most effective biological treatment option after the failure of a first TNFi treatment in a patient with rheumatoid arthritis (RA) is still unknown. Objectives: The objective of this study was to compare the effectiveness of three treatment options: abatacept, rituximab and a second TNFi, after the failure of a TNFi treatment, in patients with RA. Methods: The inclusion criteria for this pragmatic randomized controlled trial were: failing of the first TNFi, a DAS28 >3.2, not treated before with abatacept or rituximab and no contraindications for these medications. Primary outcome, the DAS28 and the secondary outcomes, HAQ-DI and SF36, were analyzed by linear mixed models to find differences over time. We corrected for possible confounders. Suspected Unexpected Serious Adverse Reactions (SUSAR) and Serious Adverse Reactions (SAR) were collected. Results: Of 144 randomized patients, 8 did not start the treatment due to infections, withdrawn from the study or did not want to start the medication. 136 started in one of the three treatment arms; 42 on abatacept (mean age=56.2 yrs, female=88.1%, median disease duration=7.1 yrs, rheumatoid factor (RF) positive=51.4%, mean baseline DAS28=4.7); 44 on rituximab (mean age=56.7 yrs, female=63.6%, median disease duration=7.6 yrs, RF positive=79.1% mean baseline DAS28=4.9); and 50 on a second TNFi (mean age=56.2 yrs, female=74.0%, median disease duration=5.6 yrs, RF positive=55.8% mean baseline DAS28=4.9). Gender and RF are significantly different between the groups (p=0.032 and p=0.020 respectively). The mean DAS28 at 6 and 12 month respectively were 4.05 and 3.85 for abatacept, 3.85 and 3.40 for rituximab and 3.70 and 3.50 for a second TNFi. No significant differences in effectiveness between the three treatment options over time (mixed models) were found in one of the outcome variables. The figure shows the DAS28 and HAQ-DI over time. One SUSAR occurred during one year follow-up. A patient in the abatacept group got a psychosis four months after the start of the study. Three SARs occurred within one year after start of the study: one salmonella infection and one pneumonia in the rituximab group and one pneumonia in the TNFi group. However, these SARs were no reason to change or stop medication. Conclusions: Although during a follow up of 1 year some small differences in DAS28, HAQ-DI and SF36 were seen between abatacept, rituximab, and a second TNFi after failure of the first TNFi, these differences were not significant. So if effectiveness is the only interest, abatacept, rituximab and TNFi seem probably equally effective after failure of the first TNFi. No substantial differences with respect to safety were observed between these three treatment groups. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1635